2014
DOI: 10.1155/2014/942834
|View full text |Cite
|
Sign up to set email alerts
|

Is There Deep-Seated Subsidence in the Houston-Galveston Area?

Abstract: Long-term continuous groundwater level and land subsidence monitoring in the Houston-Galveston area indicates that, during the past two decades (1993–2012), the groundwater head has been increasing and the overall land subsidence rate has been decreasing. Assuming that the hydraulic head in the aquifer will reach or exceed the preconsolidation level in the near future, will subsidence in the Houston-Galveston area eventually cease? The key to answer this question is to identify if there is deep-seated subsiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Both ROD1 and TXCN indicate long-term subsidence. According to our previous studies on the current subsidence in the greater Houston metropolitan area (Kearns et al, 2015;Yu et al, 2014), a rapid-subsidence bowl is forming around The Woodlands area. The Woodlands is a vibrant and fast-growing business and entertainment suburban area located 43 km north of downtown Houston (Fig.…”
Section: Horizontal Ground Deformationmentioning
confidence: 99%
See 2 more Smart Citations
“…Both ROD1 and TXCN indicate long-term subsidence. According to our previous studies on the current subsidence in the greater Houston metropolitan area (Kearns et al, 2015;Yu et al, 2014), a rapid-subsidence bowl is forming around The Woodlands area. The Woodlands is a vibrant and fast-growing business and entertainment suburban area located 43 km north of downtown Houston (Fig.…”
Section: Horizontal Ground Deformationmentioning
confidence: 99%
“…The near-coast areas could be affected by subsidence and coastal erosion problems (Simms et al, 2013;Williams et al, 1997;Yu et al, 2014). Accordingly, it is preferred that reference stations be located inland rather than within nearcoast areas.…”
Section: Stable Gulf Of Mexico Reference Frame (Sgmrf)mentioning
confidence: 99%
See 1 more Smart Citation
“…The USGS has been operating 13 borehole extensometers at 11 sites since 1973 for the purpose of observing compaction of aquifers in the whole area. The borehole extensometers, which were designed according to the sliding-joint casing type, span a depth down to 936 m [Yu et al, 2014]. Shanghai is the first city in China where land subsidence was investigated and monitored, being one of the country's most densely populated and developed areas.…”
Section: 1002/2014wr016841mentioning
confidence: 99%
“…This is primarily attributed to highly precise satellite orbit and clock data provided by the International Global Navigation Satellite System (GNSS) Service (IGS, http://www.igs.org), and new algorithms used to resolve phase ambiguity with a single receiver. The PPP method has attracted broad interests in ground deformation monitoring because of its operational simplicity and high accuracy (e.g., Wang 2013;Wang and Soler, 2014;Yu et al, 2014). Our recent GPS study indicated that the repeatability (RMS) of the daily ambiguityresolved PPP solutions achieved 2-3 mm in the horizontal components and 6-8 mm in the vertical component within the Houston metropolitan area .…”
Section: Stable Houston Reference Frame Of 2014 (Shrf14)mentioning
confidence: 99%